Prevalence of COVID-19 infection among dental and nursing students in Alappuzha - V. S., Viswakala; Sivadasan, Amrutha M.; Philip, Sairu; Karthikeyan, Sarath Thekkethil; Ahmed, Salma; Ali Edavazhikkal, Sameeha Mohamed; Kalappurakkunnel, Roshan Thankappen; Kizhakke Veetil, Saranya Raveendran; Thecheri, Sanaa; Vishnu Bhavanam, Reshma Beena; Navas, Safna Sheeja; Mohammed, Shahana; et al. (International Journal Of Community Medicine And Public Health, 2023)
Background: The Corona Virus (SARS-COV2) is one of the major pathogens that affect the human respiratory system. As it spreads via droplets, healthcare workers are at increased risk of acquiring the infection. Nursing students who are exposed to the hospital setting during their clinical postings are prone to infection because they may provide care to patients who are suspected of or diagnosed with COVID-19 infection. In dentistry, the use of hand pieces and ultrasonic instruments during dental procedures unavoidably result in generation of blood and saliva droplets. Objective was to estimate the prevalence of COVID-19 infection among Dental and Nursing students of Government dental college and nursing college, Alappuzha. Methods: A cross sectional study was conducted in Dental and Nursing students of Government TD Dental College and Nursing College, Alappuzha in November 2021. Convenient sampling was done and persons who were willing to take part in the study were distributed with a pretested questionnaire via Google Form and data was collected and analysed. Results: Out of the 174 study participants, 77 were Dental students and 97 were Nursing students, 33% of Dental students and 36% of Nursing students reported of being infected with COVID-19 virus. Significant association was obtained between COVID-19 infection and contact with Covid positive case. Conclusions: Prevalence of COVID-19 infection among Dental and Nursing students was 35.10%. Prevalence of COVID-19 infection among Dental students and Nursing students were 33% and 36% respectively.